Designing thermally sensitive public spaces: an analysis through urban design media. Issue 1 (2nd January 2023) - Requena-Ruiz, Ignacio; Siret, Daniel; Stavropulos-Laffaille, Xenia; Leduc, Thomas
ABSTRACT: Urban designers face the challenge of preserving urban life by creating public spaces that are resilient to rising temperatures. This paper studies the dissemination of urban designs specific to summer ('urban coolspots') throughout urban design media. First, the study of an inventory of urban coolspots (182 references) delineates their urban context, the main actors and principal cooling techniques. Second, a typological analysis of the projects' spatio-climatic set-ups highlights four trends as presented in the media. Finally, this article discusses the contributions of the media to an emerging urban design field and establishing an aesthetic of freshness in public space.